EFEITOS DO ACOMPANHAMENTO DO SERVIÇO DE PROTEÇÃO E ATENDIMENTO INTEGRAL À FAMÍLIA (PAIF) EM VITÓRIA/ES: UMA ANÁLISE COLETIVA - Vasconcelos, Christiane Merces (2020)
From the Federal Constitution enacted in 1988, social assistance is inserted in the field of public policies, which represented a victory in the area of social assistance, which started to be designed and executed by the state power as a right of the popu